TASK-BASED LANGUAGE LEARNING IN VIETNAMESE EFL HIGH SCHOOL CLASSROOMS: TEACHERS’ ROLES IN THE DURING-TASK PHASE AND THEIR BELIEFS - Nguyen, Thi Bao Trang (VNU Journal of Foreign Studies, 2024)
This article explored the roles the Vietnamese English as a foreign language (EFL) teachers performed during students’ task work. Data were collected over the course of 10 weeks in a Vietnamese high school where nine Vietnamese EFL teachers and their nine respective classes were observed and audio and video recorded. The teachers were also interviewed after the observed lessons. For the present paper, the teacher’s talks during student-student task execution in normal classroom schedules were audio recorded and analysed by microgenesis method. The results demonstrated a wide array of emerging fluid pedagogical roles the teachers played in response to the unfolding task work at hand. The different roles the teachers adopted were underpinned by their beliefs, awareness and thoughts. The study offers practical implications for how teachers could mediate task-based learning in EFL classroom contexts and perhaps in similar settings.